The Influence of the Direct Instruction Model Assisted by Flashcard Media on the Reading Skill of First Grade Students at SD Negeri 188 Pekanbaru - Emzira Asha Zulaifa; Dede Permana; Otang Kurniaman (Raja Zulkarnain Education Foundation, 2026)
This study aims to examine the effect of the Direct Instruction model assisted by flashcard media on the reading skills of first-grade elementary school students. The research was conducted at SD Negeri 188 Pekanbaru during the odd semester of the 2025/2026 academic year. The population consisted of all first-grade students, with a sample of 29 students, comprising 18 boys and 11 girls. This study employed a quantitative approach using a pre-experimental method with a one group pretest-posttest design. The research instrument was a reading skills test covering indicators such as letter and sound recognition, reading syllables and simple words, readng simple sentences, pronunciation accuracy, intonation and articulacion, voice clarity, reading fluency, confidence and attitude, and reading comprehension. Observation and documentatiton were used as supporting data collection techniques. Data analysis was conducted using descripstive and inferential statistical techniques, including normality testing, homogeneity testing, correlation analysis, and N-Gain analysis to measure the improvement in students’ reading skills. The results showed that the average reading skill score increased from 50,79 in the pretest to 69,76 in the posttest. Statistical analysis indicated a positive and significant effect of the direct instruction model assisted by flashcard media on students’ reading skills. Therefore, the Direct Instruction model supported by flashcard is effective and can be used as an alternative instructional strategy to improve early reading skills in elementary schools.